Lewis Acid Catalyzed Carbonyl–Olefin Metathesis - Ludwig, Jacob R.; Schindler, Corinna S. (Synlett, 2017)
Olefin–olefin metathesis has led to important advances in diverse fields of research, including synthetic chemistry, materials science, and chemical biology. The corresponding carbonyl–olefin metathesis also enables direct carbon–carbon bond formation from readily available precursors, however, currently available synthetic procedures are significantly less advanced. This Synpacts article provides an overview of recent achievements in the field of Lewis acid mediated and Lewis acid catalyzed carbonyl–olefin metathesis reactions.1 Lewis Acid Mediated Carbonyl–Olefin Metathesis2 Lewis Acid Catalyzed Carbonyl–Olefin Metathesis
Keywords: carbonyl–olefin metathesis; Lewis acid; iron; base metal